Discourse Network Analysis in Cigarette Control in Banda Aceh - Ziliwu, Delvita Andriani; Kamar, Said Amirul (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Abstract Tobacco control policy in Banda Aceh has a strong normative foundation through Law and Qanun on Smoke-Free Areas (KTR), yet the reality shows persistently high smoking rates, widespread KTR violations, weak law enforcement, and no effective policy. The novelty of this research is the application of Discourse Network Analysis (DNA) to map the discourse network of tobacco control in Banda Aceh within the context of Islamic Sharia, which has never been done before. This research is empirical legal research with a qualitative approach using DNA. Primary data were obtained from observation and public forum documentation, while secondary data came from regulations, media reports, and scientific publications. Data were analyzed through thematic coding and network mapping using DNA software. The findings identify three discourse coalitions the coalition of the Health Office and MPU with Sharia-based health narratives, the coalition of coffee shop traders and cigarette retailers with grassroots economic narratives, and the ambivalent position of the city government. The study also found the weakness of anti-smoking NGO coalitions due to perceptions of foreign funding and the absence of women's narratives in public discourse. The implication is the need for cross-actor dialogue and evaluation of the KTR Qanun.